(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This study explores how consumers view customized health insurance and how technology facilitates efficient human-machine communication for customized insurance plans. It looks at how customer behaviour is affected by technological interfaces, specifically how ready they are to reveal personal information and use digital platforms to make insurance decisions. The study also assesses if technology-enabled customisation boosts health insurance industry sales. To gather primary data, a mixed-methods approach was used, combining structured interviews and online surveys with secondary research from industry sources. Customers’ interest in tailored insurance options and their openness to technology are positively correlated, according to the findings of this paper. The lack of a statistically significant correlation between customisation and actual sales, however, raises the possibility that other variables, such privacy concerns, ignorance, or discontent with the available alternatives, could limit the influence of personalization on sales. Notwithstanding this disparity, the results highlight the increasing significance of technology-driven customization in health insurance. It is anticipated that customized insurance solutions would become more popular as customers get more tech-savvy and at ease with interacting with machines.